CONCEPTUALIZING THE ROLE OF KAHOOT! IN ENHANCING FORMATIVE ASSESSMENT PRACTICES IN EFL - Yustisio, Armaz; Arif Suryo Priyatmojo (Universitas PGRI Palembang, 2025)
This chapter explores how Kahoot! can be used as a tool for formative assessment in the English as a Foreign Language (EFL) classroom. The chapter uses the key ideas of assessment, feedback and self-regulated learning to see how this platform aligns with the principles of effective teaching. The chapter argues that Kahoot! is great for increasing student motivation and giving teachers quick feedback to adjust their lessons. However, the chapter also highlights key challenges. The platform's feedback is often too simple, it cannot evaluate skills such as speaking or writing, and the focus on speed and competition can hinder deep thinking. To help teachers, the chapter presents a model called ‘Gamified Formative Assessment’ that shows how to use Kahoot!'s strengths while managing its weaknesses. The main conclusion is that Kahoot! is not effective on its own. Its true value depends on how a teacher thoughtfully and strategically uses it as a meaningful part of their overall assessment plan.